The influenza pandemic and Europe: the social impact and public health response (Italian Journal of Public Health, 2009)
Influenza is unpredictable. It is a virus thatspreads globally and each season viruses emergewith different virological, clinical and epidemiological characteristics. Usually influenza affects 5-20% [1] of the population but sometimes a pandemic virus emerges which spreads on a worldwide scale and infects a larger proportion of the human population.On 11 June 2009 WHO announced that the world was confronted with a pandemic virus – pandemic (H1N1) 2009 virus. This virus was first detected in two children in the United States in March 2009 but had its epidemiological origins in Mexico City in January-March 2009 [2]. The virusquickly spread to the US and Canada, and then further afield. In the European Union and EEA countries, there are currently 9453 cases and four deaths and globally there are now over 79,000 cases and 332 deaths (3 July 2009) [3].